Proton pump inhibitor therapy and risk of knee replacement surgery: a general population-based cohort study. Issue 4 (April 2022) - Zeng, C.; Neogi, T.; Chan, A.T.; Wei, J.; Misra, D.; Lu, N.; Choi, H.K.; Lei, G.; Zhang, Y.
Summary: Objective: Proton pump inhibitors (PPIs) are among the most commonly used medications for patients with osteoarthritis (OA). Various types of PPIs have different impacts on lowering serum magnesium level that may affect knee OA progression. We aimed to compare the risk of clinically relevant endpoint of knee replacement (KR) among initiators of five different PPIs with that among histamine-2 receptor antagonist (H2RA) initiators. Design: Among patients with knee OA (≥50 years) in The Health Improvement Network database in the UK we conducted five sequential propensity-score matched cohort studies to compare the risk of KR over 5-year among patients who initiated omeprazole ( n  = 2, 672), pantoprazole ( n  = 664), lansoprazole ( n  = 3, 747), rabeprazole ( n  = 751), or esomeprazole ( n  = 827) with those who initiated H2RA. Results: The prevalence of PPI prescriptions among participants with knee OA increased from 12.7% in 2000–44.0% in 2017. Two-hundred-and-seventy-four KRs (30.8/1, 000 person-years) occurred in omeprazole initiators and 230 KRs (25.4/1, 000 person-years) in H2RA initiators. Compared with H2RA initiators, the risk of KR was 21% higher in omeprazole initiators (hazard ratio [HR] = 1.21, 95% confidence interval [CI]:1.01–1.44). Similar results were observed when pantoprazole use was compared with H2RA use (HR = 1.38, 95%CI:1.00–1.90). No such an increased risk of KR was observed among lansoprazole (HR = 1.06, 95%CI:0.92–1.23), rabeprazole (HR = 0.97, 95%CI:0.73–1.30), or esomeprazole (HR = 0.83, 95%CI:0.60–1.15) initiators compared with that among H2RA initiators. Conclusions: In this population-based cohort study, initiation of omeprazole or pantoprazole use was associated with a higher risk of KR than initiation of H2RA use. This study raises concern regarding an unexpected risk of omeprazole and pantoprazole on accelerating OA progression.